Financial stability assessment for EU candidate countries and potential candidates: Developments since 2016 - Mariarosaria Comunale; André Geis; Ioannis Gkrintzalis; Isabella Moder; Éva Katalin Polgár; Lucia Quaglietti; Li Savelin (European Central Bank (ECB), 2019)
This paper reviews and assesses financial stability challenges in countries preparing for EU membership, i.e. Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia, Serbia and Turkey. The paper mainly focuses on the period since 2016 (unless the analysis requires a longer time span) and on the banking sectors that dominate financial systems in this group of countries. For the Western Balkans, the paper analyses recent trends in financial intermediation, as well as the two main challenges that have been identified in the past. Asset quality continues to improve, but the share of non-performing loans is still high in some countries, while regulatory, legal and tax impediments are still to be resolved in most cases. High unofficial euroisation is a source of indirect credit risk for countries with their own national legal tender, which calls for continued efforts to promote the use of domestic currencies in the financial system. At the same time, banking systems seem less prone to financial stress from maturity mismatches than certain EU peers. These risks are met with a solid shock-absorbing capacity in the Western Balkans, as exemplified by robust capital and liquidity buffers. Turkey experienced a period of heightened financial stress during 2018 and, while its banking system appears to have sufficient buffers to absorb shocks overall, significant forex borrowing of corporates and high rollover needs of banks in foreign exchange on the wholesale market constitute considerable financial stability risks.
Keywords: F31; F34; F36; G15; G21; G28; 330; Banking sector; financial stability; foreign exchange lending; credit growth; non-performing loans; EU accession; Western Balkans; Turkey